Band-edge mediated frequency down-conversion in a gas-filled anti-resonant hollow-core fiber - Gavara, Trivikramarao (2022)
We demonstrate frequency down-conversions of femtosecond pulses through dispersive wave generation and degenerate four-wave mixing in a gas-filled anti-resonant hollow-core fiber. These are achieved by exploiting the rapid variation of the dispersion in the fiber’s transmission band edge. In this approach, the wavelength of the down-shifted radiation is governed solely by the thickness of the dielectric wall at the core–cladding interface, while other system parameters are accountable only for inducing sufficient nonlinear phase shifts. With the right choice of cladding wall thickness, the concept can be applied directly for generating high-power mid-infrared femtosecond pulses.